«Великий терор» на Полтавщині (за матеріалами Галузевого державного архіву Служби безпеки України) - Бажан, О. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
Based on the unknown documents from the archive of Security service of Ukraine, the author investigated to what results led the fulfillment of executive orders of the NKVD in Poltava region.